2014
DOI: 10.1590/s1806-66902014000300016
|View full text |Cite
|
Sign up to set email alerts
|

Action of rain on the efficiency of herbicides applied post-emergence in the control of Senna obtusifolia

Abstract: -The objective of this study was to evaluate the effect of rainfall on the effectiveness of herbicides applied post-emergence on plants of Senna obtusifolia. The experiment was carried out under green-house conditions and the experimental design was completely randomized design with four replications, with treatments in a 7x8 factorial arrangement (seven herbicides treatments and eight rain intervals). The herbicides used were five formulations of glyphosate (Roundup Original, Roundup WG, Roundup Transorb, Rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
1
0
4
Order By: Relevance
“…No caso dos herbicidas hidrofílicos (baixo Kow, como o glyphosate), a água de hidratação da cutícula e os filamentos de pectina dispersos na matriz da cutina (Velini et al, 2009) são as principais rotas de penetração desse herbicida, assim devido a essa condição, a retenção e a absorção da molécula de glyphosate foi prejudicada em plantas de mucuna-preta. Segundo ( Barnes & Oliver, 2003) e 1080 g ha -1 (Souza et al, 2014) de glyphosate provocou sintomas de fitointoxicação superiores a 80% aos 7 e 14 DAA, respectivamente. Já ao avaliar a seletividade de espécies nativas como a acácia-monjolo (Acacia polyphylla DC.)…”
Section: Resultsunclassified
“…No caso dos herbicidas hidrofílicos (baixo Kow, como o glyphosate), a água de hidratação da cutícula e os filamentos de pectina dispersos na matriz da cutina (Velini et al, 2009) são as principais rotas de penetração desse herbicida, assim devido a essa condição, a retenção e a absorção da molécula de glyphosate foi prejudicada em plantas de mucuna-preta. Segundo ( Barnes & Oliver, 2003) e 1080 g ha -1 (Souza et al, 2014) de glyphosate provocou sintomas de fitointoxicação superiores a 80% aos 7 e 14 DAA, respectivamente. Já ao avaliar a seletividade de espécies nativas como a acácia-monjolo (Acacia polyphylla DC.)…”
Section: Resultsunclassified
“…Berdasarkan realita perkembangan gulma sangat cepat, seperti yang ditunjukkan oleh gulma Ryegrass (Lolium rigidum) di Australia yang mampu memproduksi 1.000 anakan per tanaman (Saini et al, 2015). Hasil penelitian di Brazil tentang pengaruh gulma terhadap produksi kedelai * Corresponding author: tumiar.katarina@fp.unila.ac.id menunjukkan kehadiran gulma Senna obtusifolia (L) terbukti telah menurunkan produksi kedelai hingga mencapai 30% (Souza et al, 2014). Dampak negatif lain yang ditimbulkan gulma yaitu dapat menjadi inang bagi hama dan penyakit tanaman (Ntidi et al, 2016;Sembodo, 2010;Thompson et al, 2018).…”
Section: Pendahuluanunclassified
“…Kemudian ditranslokasikan pada seluruh jaringan hidup dan pembuluh floem menuju ke jaringan meristem secara sistemik. Karena itu efikasi dari herbisida sangat berkaitan dengan lama proses penyerapan (Ganie et al, 2017;Souza et al, 2014).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Studies conducted to demonstrate the effects of rain on the efficacy of glyphosate after post-emergence application have shown that this herbicide decreases its control efficiency when rain occurs soon after its application (MARTINI et al, 2003;SOUZA et al, 2013;2014). However, control efficacy is also directly influenced by the various formulations available in the market and by the dose used (FENG et al, 2000;MONQUERO;SILVA, 2007).…”
Section: Introductionmentioning
confidence: 99%